Surface Conditioning Treatments for Improving Adhesion of Fiber Posts - Modgi, Chetan Mukund; Ajay, Aras Meena; Chitre, Vidya (Journal of Orofacial Research, 2012)
The restoration of endodontically treated teeth has been studied extensively. Posts are widely used for the restoration of these teeth when there is insufficient coronal tooth structure to retain a core for the definitive restoration. Prefabricated postsystems have become more popular because they can provide satisfactory results with less chairside time. Bonding of fiber posts to composite materials relies only on the chemical interaction between the postsurface and the resin material used for luting or building-up the core. In an attempt to maximize resin bonding to fiber posts, several surface treatments have been recently suggested. The aim of this review is to focus on these surface treatments in detail.